'I have the world's best job' – staff experience of the advantages of caring for older people. Issue 2 (12th August 2015) - Eldh, Ann Catrine; van der Zijpp, Teatske; McMullan, Christel; McCormack, Brendan; Seers, Kate; Rycroft‐Malone, Jo
Abstract : Rationale: Besides a growing demand for safe high‐quality care for older people, long‐term care (LTC) often struggles to recruit appropriately qualified nursing staff. Understanding what LTC staff value in their work may contribute to a more comprehensive understanding of what can attract staff and support person‐centred care. Aim: To explore staff experience of the advantages of working in LTC settings for older people. Methods: Narrative descriptions of 85 LTC staff in Ireland, the Netherlands and Sweden on what they value in their work were analysed with qualitative content analysis. Ethics: Ethical approval was obtained according to the requirements of each country, and participants provided informed consent prior to the individual interviews. Findings: Working in LTC signifies bonding with the older people residing there, their next of kin and the team members. It means autonomy in one's daily tasks amalgamated with being a part of an affirmative team. Participants reported a sense of accomplishment and fulfilment; caring meant consideration and recognition of the older people and the relationships formed, which provided for professional and personal growth. The sharing of compassion between staff and residents indicated reciprocity of the relationship with residents. Study limitations: The findings may be transferable to LTC in general although they address only the positive aspects of caring for older people and only the experiences of those staff who had consented to take part in the study. Conclusions: The findings add to what underpins the quality of care in nursing homes: compassion in the nurse–resident relationship and person‐centred care in LTC. They indicate reciprocity in the relations formed that may contribute to the empowerment of older people, but further studies are needed to explore this in more detail.